2016
DOI: 10.1002/anie.201601703
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Crystalline Polar Polyethylene: Ester‐Functionalized Linear Polyolefins Enabled by a Functional‐Group‐Tolerant, Cationic Nickel Catalyst

Abstract: A dibenzobarrelene-bridged, α-diimine Ni(II) catalyst (rac-3) was synthesized and shown to have exceptional behavior for the polymerization of ethylene. The catalyst afforded high molecular weight polyethylenes with narrow dispersities and degrees of branching much lower than those made by related α-diimine nickel catalysts. Catalyst rac-3 demonstrated living behavior at room temperature, produced linear polyethylene (Tm =135 °C) at -20 °C, and, most importantly, was able to copolymerize ethylene with the bior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(122 citation statements)
references
References 104 publications
2
104
1
Order By: Relevance
“…) . As a note, a related Ni α ‐diimine catalyst containing an unsubstituted dibenzobarrelene backbone was previously reported by Coates and co‐workers, and was shown to polymerize ethylene in a living manner at room temperature . However, Wu and co‐workers recently discovered that by symmetrically substituting the dibenzobarrellene backbone framework with bulky t ‐butyl groups, an even greater enhancement in thermal stability could be realized.…”
Section: Thermally Stable Ni‐ and Pd‐based Catalystsmentioning
confidence: 95%
“…) . As a note, a related Ni α ‐diimine catalyst containing an unsubstituted dibenzobarrelene backbone was previously reported by Coates and co‐workers, and was shown to polymerize ethylene in a living manner at room temperature . However, Wu and co‐workers recently discovered that by symmetrically substituting the dibenzobarrellene backbone framework with bulky t ‐butyl groups, an even greater enhancement in thermal stability could be realized.…”
Section: Thermally Stable Ni‐ and Pd‐based Catalystsmentioning
confidence: 95%
“…This steric effect may be the key factor in the differences between the two sets of catalysts with different connectivity to the naphthalene backbone. [50]. Our groups showed that some sterically very bulky phosphine-sulfonate nickel catalysts could copolymerize ethylene with various polar monomers [51].…”
Section: Pd2" 9 25mentioning
confidence: 97%
“…[41] Considering the impressive reactivity of the Brookhart catalysts toward norbornene, [42] and their excellent tolerance toward ester functionalities,C hen and co-workers successfully copolymerized ethylene with polar functionalized norbornenes using a-diimine palladium catalysts. [43,44] Coates and co-workers [45] and Gao and co-workers [46] demonstrated that a-diimine nickel catalysts can mediate ethylene copolymerization with methyl 10-undecenoate.…”
Section: Developments Using the Brookhart And Drent Catalystsmentioning
confidence: 99%